Modelling of fluidized bed channelling using a two-zone model - Machač, Ivan; Šiška, Bedřich; Simon, Miloslav (University of Pardubice, 2016)
This paper deals with the study of the structure of spherical particle beds fluidized with non-Newtonian aqueous polymer solutions in the creeping flow region in a two-dimensional rectangular column. It was confirmed that in fluidization with viscoelastic polymer solutions the bed chanelling occurs and bed expansion reduces. A simple two-zone model was used to describe the bed channeling.